Primary Breast Sarcoma - Ondinee Manalo Igot Mary; Y. Fernando Gracieux (Journal of Clinical Case Reports and Images, 2022)
Introduction Primary sarcomas of the breast are <0.1% of all malignant tumours of the breast. To date, there are 13 major breast sarcoma series in English literature. This study adds to these series characterizing primary breast sarcoma among Philippine patients. Methods All breast biopsies from the pathology records of the University of the Philippines-Philippine General Hospital (UP-PGH) were searched for breast sarcoma cases from January 2000 to December 2010. Metaplastic carcinomas and phyllodes tumors were excluded. Results There were 52 patients (45 female, 7 male) ranging in age 25-83 years (median 46 years). Majority had lump, ten cases with pain. No history of previous cancer was given. No history of prior radiation was found. Histopathological diagnoses were spindle cell sarcoma (n=13), fibrosarcoma (n=6), liposarcoma (n=6), MPNST (n=5), stromal sarcoma (n=5), angiosarcoma (n=4), MFH (n=4), leiomyosarcoma (n=3), rhabdomyosarcoma (n=3), chondrosarcoma (n=2), and synovial sarcoma (n=1). Tumors were with grade 1 (n=18), grade 2 (n=8), and grade 3 (n=10). Necrosis was noted in 6 cases. Simple mastectomy was done in 19 cases (37%), MRM in 31 cases (59%), while 2 far advanced had no surgery (3%). None had adjuvant radiotherapy or chemotherapy. The duration of follow-up for 45 patients ranged from 1 – 117 months, excluding those who were lost to follow-up. All 15 deaths were due to progressive disease. Recurrences were observed in 9 patients. The disease-free survival (DFS) and overall survival (OS) was 73%and 75%, respectively. On multivariate analysis, DFS and OS were significantly correlated with size (HR=113.63; p=0.019 and HR=77.36; p=0.037), grade (HR=20.73 ; p=0.003andHR= 39.57; p= 0.004), and having a histology of angiosarcoma (HR=35.20 ; p=0.005and HR= 50.74; p=0.007), respectively. Conclusion Sarcoma remains an important clinical entity among primary breast cancers.
Keywords: Primary breast sarcoma